TENSION OF THE REGIONAL LABOUR MARKET AS THE FACTOR DETERMINING THE STRATEGY OF ITS REGULATION - N. A. Biksina (Russian Journal of Economics and Law)
The article gives a brief characteristic of the regional labour market, views the specific features of the regional labour market and factors determining it. The technique is presented for estimating the critical level of the condition in the regional labour market.